Improving Students Activity and Students Learning Outcomes by Using Cooperative Learning with Trade a Problem type - Yuli Asi Arianto; Abd Rahman (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2020)
The purpose of the research to describe learning model of trade a problem can improve the students’ activities. To describe learning model of trade a problem can improve the students learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIIA at MTs Al Mujahidi Tembokrejo. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is there is improving activity and student learning outcomes.Keywords: trade a problem, students activity, and learning outcome